Foams generated from viscous non-Newtonian shear-thinning liquids in a continuous multi rotor-stator device. (January 2020) - Jabarkhyl, Saifullah; Barigou, Mostafa; Zhu, Shiping; Rayment, Pip; Lloyd, David M.; Rossetti, Damiano
Abstract: Whilst aeration is ubiquitous in the food industry, little work has been done on foams generated from viscous non-Newtonian liquids. We study the production of foams from viscous shear-thinning liquids containing a non-ionic food grade surfactant (PGE 55), Xanthan gum and caster sugar, using a continuous pilot-scale device having twelve rotor-stator pairs. The effects of process parameters (rotor speed, gas-liquid volumetric flowrate ratio (G/L)) and liquid composition (surfactant concentration, Xanthan gum concentration) on foam gas volume fraction and bubble size distribution are elucidated. X-ray micro-Computed Tomography is employed to characterise the 3D microstructure of the foams. Rotor speed and G/L ratio are the dominant factors in determining the gas volume fraction and bubble size distribution. The foams produced exhibit a rich fine texture with high static stability. For a given energy input in turbulent flow, a higher G/L ratio results in a higher gas fraction and a smaller bubble size. Industrial relevance: Aeration is ubiquitous in the food industry and innovative ways to generate stable foams with fine texture from viscous non-Newtonian media are needed to satisfy the increasing demand for better quality, healthier and cheaper products. The use of continuous multi rotor-stator devices operating in turbulent flow and under atmospheric pressure achieves optimum aeration efficiency and prevents foam expansion. The use of an effective surfactant such as PGE 55 and a thickener such as Xanthan gum help provide the desired fine texture and stability for longer shelf-life. Operating at high gas-liquid ratios in turbulent flow achieves the production of finer more uniform foams with less energy input. Highlights: A multi rotor-stator device is effective for producing foams in highly viscous media. Hydrodynamic conditions and liquid formulation are critical to aeration efficiency. PGE 55 and XG enable generation of stable foam in a continuous rotor-stator device. Rotor speed and dispersion viscosity are critical to foam microstructure and stability. Energy consumption efficiency improves for foams with higher gas to liquid ratios.